Trident: From High-Level Language to Hardware Circuity. - Tripp, Justin L.; Gokhale, Maya B.; Peterson, Kristopher D. (Computer (00189162), 2007)
The article discusses the computer program Trident and how it can be used to aid reconfigurable supercomputing. Traditionally, reconfigurable supercomputers used field-programmable gate arrays alongside high-performance microprocessors in clusters. More recently, floating-point libraries, computational kernels, and applications have been used. The kernels and applications, while providing a much higher performance level, must be hand-coded in a hardware description language (HDL). The author contends that using a high level language (HLL) translated fixed and floating point algorithms is a better option. Trident synthesizes circuits from an HLL, using an open framework that allows the programmer to define new floating-point operations easily.